“Jarak yang Memisahkan Kau dan Aku” Studi Fenomenologi Pengalaman Suami Tenaga Kerja Wanita yang Menjalani Pernikahan Jarak Jauh (Long Distance Marriage) - Harini Edgina Mariana Bangngu (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2022)
In this day and age, many married couples do not live together and undergo long-distance marriages, as in the case of female workers. One of the causative factors is the economy, and it affects marital satisfaction. According to Fower Olson (1993), marital satisfaction is a husband or wife's subjective evaluation of their married life based on feelings of satisfaction, happiness, and pleasant experiences with their partner. The purpose of this study was to determine the married life of the female workforce couple and their dynamics on marital satisfaction felt by their husbands. This research is phenomenological research with the method of Interpretative Phenomenological Analysis (IPA). Data collection techniques through interviews on a research subject. The results of the study found that long-distance marriages occur because they want to find business capital. The length of the relationship makes the subject understand the conditions of his marriage so that it can overcome various problems that arise, and requires the subject to make efforts to solve them, namely maintaining communication, accepting the consequences and maintaining commitment.